2000
DOI: 10.1038/sj.cgt.7700225
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer to hepatocellular carcinoma: Transduction efficacy and transgene expression kinetics by using retroviral and lentiviral vectors

Abstract: Gene therapy is an attractive therapy for hepatocarcinoma, and several approaches have been studied using murine leukemia virus-derived retroviruses. We compared gene transfer efficacy and transgene expression kinetics after transduction of hepatocarcinoma cell lines using enhanced green fluorescent protein (EGFP)-expressing murine leukemia virus-derived retroviral vectors and HIV-derived lentiviral vectors. First, we showed that both retroviral and lentiviral vectors efficiently transduce cycling hepatocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 18 publications
(22 reference statements)
2
35
0
Order By: Relevance
“…Although LV genomes contain an extremely low level of CpG dinucleotides [88], the ablation of these remaining sequences may favor a potential elevation of transcription. As an example, the use of SIN-derived LV vectors that do not contain the U3 LTR region has allowed sustained expression of the transgene [89,90]. A recent report has shown that the transcriptional silencing in murine cells of HIV-1-derived vectors was limited to non-SIN transfer backbones that still generate LTR-mediated transcription and therefore participate in promoter interference [91].…”
Section: Modulation Of the Transcriptional Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LV genomes contain an extremely low level of CpG dinucleotides [88], the ablation of these remaining sequences may favor a potential elevation of transcription. As an example, the use of SIN-derived LV vectors that do not contain the U3 LTR region has allowed sustained expression of the transgene [89,90]. A recent report has shown that the transcriptional silencing in murine cells of HIV-1-derived vectors was limited to non-SIN transfer backbones that still generate LTR-mediated transcription and therefore participate in promoter interference [91].…”
Section: Modulation Of the Transcriptional Silencingmentioning
confidence: 99%
“…In addition, the choice of the ideal promoter should be seriously envisaged for optimal long-term expression performance. As an example, the benefit in terms of sustainable expression activity of the human phosphoglycerate kinase promoter (hPGK) over the cis-active promoting region of the cytomegalovirus (CMV) has been clearly demonstrated in the hepatocyte transduction model [89]. Additional heterologous promoter elements such as those derived from virus genomes have participated in an enhancement of the long-term transgene expression.…”
Section: Modulation Of the Transcriptional Silencingmentioning
confidence: 99%
“…Lentiviral vectors are retroviral vectors, which, in some instances, have been shown to be able to transduce low-or nonproliferating cells such as neurons, nonstimulated normal hepatocytes or growth-arrested HCC cells conversely to MLV-derived vectors. [49][50][51][52][53][54][55] MLV-derived vectors and HIV-1-derived vectors share several features. The gag, pol and env coding sequences, along with the rev, vpr, nef, vif, vpu and tat coding sequences which encode regulatory and accessory proteins, have been eliminated from the vector backbone.…”
Section: Viral Vectorsmentioning
confidence: 99%
“…13 Technical procedures to generate lentiviral vector containing supernatants and estimate the viral titer have already been described. 14 Transduction in vitro was performed as follows. On day 1, cells were seeded at 1 Â 10 5 cells/well in 12-well dishes in culture medium containing 4 mg/ml polybrene.…”
Section: Gene Transfer Procedures and Transgene Expression Assaymentioning
confidence: 99%
“…FACS analysis of EGFP expression in genetically manipulated cells harvested from tumors or metastases showed various expression profiles, suggesting that the in vivo context does indeed strongly affect the expression kinetics of these transgene. Molecular mechanisms, including DNA hypermethylation, 14,16 mutations localized in the cDNA of the transgene or in the promoter, 17,18 the impact of the cellular protein context, 19 combined with the selection of cell populations in vivo due to a potential toxic effect of the transgene in some conditions 20 can dramatically impact the expression kinetics of the transgene. Whether these mechanisms alone or in combination can explain the modification of the EGFP expression kinetics in this model remains to be explored.…”
Section: Orthotopic Tumor Transductionmentioning
confidence: 99%